Respuesta :

Answer:

[tex]x = 6[/tex]

Step-by-step explanation:

Step 1:  Distribute

[tex]-3(x - 4) + x = 2x - 12[/tex]

[tex](-3 * x) + (-3 * -4) + x = 2x - 12[/tex]

[tex](-3x) + (12) + x = 2x - 12[/tex]

Step 2:  Combine like terms

[tex](-3x) + (12) + x = 2x - 12[/tex]

[tex](-3x + x) + 12 = 2x - 12[/tex]

[tex](-2x) + 12 = 2x - 12[/tex]

Step 3:  Add 12 to both sides

[tex](-2x) + 12 + 12 = 2x - 12 + 12[/tex]

[tex](-2x) + 24 = 2x[/tex]

Step 4:  Add 2x to both sides

[tex](-2x + 2x) + 24 = 2x + 2x[/tex]

[tex]24 = 4x[/tex]

Step 5:  Divide both sides by 4

[tex](24 / 4) = (4x / 4)[/tex]

[tex](6) = x[/tex]

Answer:  [tex]x = 6[/tex]